Discursos sobre o ensino de língua portuguesa em torno da sintaxe: relações de poder, saber e subjetivação docente - Santos, Sarah Pereira dos (Universidade Federal de Catalão, 2022)
This research aims to map the discourses about the teaching of Portuguese language with emphasis on syntax, in order to identify what are the rules of formation that constitute this knowledge. Moreover, it is hypothesized that this discursive network affects the subjectivization process of the teacher. To this end, our corpora consist of statements collected from two online magazines, Exame and Negócio, four scientific articles, three texts of laws; excerpts from the Base Nacional Comum Curricular (BNCC) and interviews with teachers of the basic network, in order to present a discursive network about this teaching of Portuguese, emphasizing, sometimes, the syntax. It is known that investigating the teaching of Portuguese language opens multiple possibilities, in view of being a broad science with many ramifications. However, we decided to focus on the teaching of syntax, since it is part of the daily lives of students and teachers in the basic education system through the teaching- learning of Portuguese, since this content appears as mandatory from the 6th grade on in the normative documents that govern educational practices in Brazil. As a methodological gesture, for data collection, it was used interviews, in semi-structured format (FLICK, 2013), with Portuguese language teachers who taught in elementary school: final years, in the 8th grade of the basic network, and, in order to develop an analytical movement about what these subjects said about their practice, this dissertation used the arquegenealogical method, a tool developed by Michel Foucault. The specific objectives are: i) to describe the rules of knowledge formation about the Portuguese language around syntax; ii)in the of teaching Portuguese and syntax;iii) to understand the effects of truth produced in the selected statements; and iv) to analyze how these discourses constitute the subject-teacher. In order to develop an archegenealogical study, this research was based on the sayings and writings of Michel Foucault, especially the notions of utterance, discourse, subject, knowledge-power, discursive memory, governmentality, truth effect, and subjectivity. The relevance of this research is intrinsically associated with the need to problematize the knowledge that is in circulation about the teaching of Portuguese language and syntax through Foucauldians discourse studies.
Discourses on Portuguese language teaching around syntax: relations of power, knowledge and teaching subjectivation
Keywords: Estudos Discursivos Foucaultianos; Saber-Poder; Subjetivação; Ensino de Língua Portuguesa; Ensino de Sintaxe; 8.00.00.00-2 Lingüística, Letras e Artes